Characteristics of droplet behaviors after the end of injection in a high-pressure constant volume chamber. (1st May 2020) - Luo, Hongliang; Wang, Chao; Nishida, Keiya; Ogata, Youichi; Chen, Run
Highlights: Mie scattering fails to capture the small size droplets. The droplets impacting on the wall is the main reason for adhesion increase AEOI. Most droplets impinging to the wall locate in the first quadrant AEOI. With spray development, Md firstly decreases then increases with better dispersion. Abstract: Many investigations on droplet behaviors during the injection were published. However, studies after the end of injection (AEOI) were seldom reported. Owing to the fuel adhesion on the wall still increases even AEOI, it is significantly important to observe the droplet behaviors for understanding the mechanisms. In this study, bottom view of fuel adhesion and side view of impinging spray were recorded through refractive index matching (RIM) method and Mie scattering observation, respectively. Morphologies of the fuel adhesion with impinging spray were shown, suggesting that even AEOI, fuel adhesion still increases on the wall. The incoming droplets in the air is supposed to be the main reason for it, although the fuel droplets were difficult to be detected through Mie scattering images. Therefore, quantitative measurement for fuel droplet was conducted by particle image analysis (PIA) technique. The microscopic behaviors of fuel droplets were obtained at 3, 5, 10 and 20 ms ASOI. Results showed that due to the small size of the droplets, Mie scattering fails to capture small droplets moving in the air AEOI. However, these small-size droplets really exit and still move towards the wall until impacting on it, which proves that after injection, droplets in the air could adhere on the wall is the main reason for adhesion increase. Furthermore, the droplets size, velocity and minimum distance distributions at different locations with different timings ASOI were analyzed in detail.